The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1128/jvi.00570-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ongoing Human Immunodeficiency Virus Type 1 (HIV-1) Replication in Residual Viremia during Recombinant HIV-1 Poxvirus Immunizations in Patients with Clinically Undetectable Viral Loads on Durable Suppressive Highly Active Antiretroviral Therapy

Abstract: In most human immunodeficiency virus type 1 (HIV-1)-infected individuals who achieve viral loads of <50 copies/ml during highly active antiretroviral therapy (HAART), low levels of plasma virus remain detectable for years by ultrasensitive methods. The relative contributions of ongoing virus replication and virus production from HIV-1 reservoirs to persistent low-level viremia during HAART remain controversial. HIV-1 vaccination of HAART-treated individuals provides a model for examining low-level viremia, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 49 publications
(71 reference statements)
0
37
0
Order By: Relevance
“…4,5,7,9,11,12,[18][19][20][21][22][23][24] Numerous studies investigating the clinical significance of MVR and the origin of residual viruses circulating in blood are ongoing and all of them are based on ultrasensitive assays quantifying HIV-1 RNA levels below 50 cp/mL. Thanks to these pioneering studies, several interesting findings have been reported.…”
Section: Discussionmentioning
confidence: 94%
“…4,5,7,9,11,12,[18][19][20][21][22][23][24] Numerous studies investigating the clinical significance of MVR and the origin of residual viruses circulating in blood are ongoing and all of them are based on ultrasensitive assays quantifying HIV-1 RNA levels below 50 cp/mL. Thanks to these pioneering studies, several interesting findings have been reported.…”
Section: Discussionmentioning
confidence: 94%
“…[12][13][14][15][16][17] Given that low intracellular ARV concentrations allow viral replication and the selection of drug-resistant HIV-1, we hypothesized that the detection of new drug resistance mutations during suppressive ART would predict subsequent virologic failure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have attempted to determine whether the source of persistent viremia during successful combination ART also results from incomplete suppression of virus replication or if residual plasma virus is produced by long-lived, chronically infected cells. Some studies indicate that low-level viral replication may occur in specific anatomical compartments despite suppression of plasma HIV-1 RNA to less than 75 copies per ml by ART (5,7,9,15,28,29,36,39), whereas others have found no evidence for ongoing HIV-1 replication during suppressive therapy (4,7,11,23,27,34,38,40). For example, studies by Dinoso et al, McMahon et al, and Gandhi et al showed no decrease in the level of persistent viremia in patients before, during, or after treatment intensi-fication with several different classes of antiretroviral compounds by using an assay with single RNA copy sensitivity, suggesting a lack of ongoing new rounds of infection during effective ART (11,14,31).…”
mentioning
confidence: 99%